2017
DOI: 10.1111/acel.12695
|View full text |Cite
|
Sign up to set email alerts
|

Brain 5‐lipoxygenase over‐expression worsens memory, synaptic integrity, and tau pathology in the P301S mice

Abstract: SummaryProgressive accumulation of highly phosphorylated tau protein isoforms is the main feature of a group of neurodegenerative diseases collectively called tauopathies. Data from human and animal models of these diseases have shown that neuroinflammation often accompanies their pathogenesis. The 5‐lipoxygenase (5LO) is an enzyme widely expressed in the brain and a source of potent pro‐inflammatory mediators, while its pharmacological inhibition modulates the phenotype of a tau transgenic mouse model, the ht… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 28 publications
(16 citation statements)
references
References 31 publications
0
16
0
Order By: Relevance
“…In this model, in vitro and in vivo studies suggest that it is 5-lipoxygenase localized at the nuclear envelope that executes ferroptosis (Karuppagounder et al, 2018). Therefore, the development of brain-penetrant inhibitors of 5-lipoxygenase that are active in mice and humans could be an effective strategy for treating parenchymal brain hemorrhage or Alzheimer's disease (Vagnozzi et al, 2018).…”
Section: Llmentioning
confidence: 99%
“…In this model, in vitro and in vivo studies suggest that it is 5-lipoxygenase localized at the nuclear envelope that executes ferroptosis (Karuppagounder et al, 2018). Therefore, the development of brain-penetrant inhibitors of 5-lipoxygenase that are active in mice and humans could be an effective strategy for treating parenchymal brain hemorrhage or Alzheimer's disease (Vagnozzi et al, 2018).…”
Section: Llmentioning
confidence: 99%
“…In addition to the effects of cytokines on kinases and phosphates, it was recently shown that metalloproteinase MMP-9 causes tau aggregation via deacetylase HDAC6 [299]. Furthermore, the leukotrine 5-Lipoxygenase is upregulated in tauopathies, worsens tau pathology, neuroinflammation, and increases synapse loss [58, 108111, 184, 300, 301]. More studies are needed to identify if and how microglia can initiate tau aggregation, rather than mere aggravation of existing tau pathology.…”
Section: Bidirectional Effects Of Tau Pathology and Microglial Neuroimentioning
confidence: 99%
“…CREB is one of the pivotal transcription factors regulating the expression of various synaptic proteins. Studies show that extracellular application of tau oligomers or direct overexpression of tau or hyperphosphorylation and accumulation of tau by various molecules all reduced synaptic protein expression and disrupted glutamate receptor trafficking (Hoover et al, ; Puzzo et al, ; Vagnozzi, Giannopoulos, & Pratico, ). By overexpression hTau in primary hippocampal neurons, the decreased protein levels of BDNF, GluN1, GluN2A, GluA1, GluA2, PSD93, PSD95, and SYT were also detected with unchanged GluN2B, SYP, and SYN1.…”
Section: Discussionmentioning
confidence: 99%